The role of H-bonds in the solid state organization of [1]benzothieno[3, 2-b][1]benzothiophene (BTBT) structures: bis(hydroxy-hexyl)-BTBT, as a functional derivative offering efficient air stable organic field effect transistors (OFETs). Issue 28 (4th July 2016) - Roche, Gilles H.; Tsai, Yu-Tang; Clevers, Simon; Thuau, Damien; Castet, Frédéric; Geerts, Yves H.; Moreau, Joël J. E.; Wantz, Guillaume; Dautel, Olivier J.
Abstract : The rapid and inexpensive functionalization of the BTBT core with hydroxyl end group functionalized hexyl chains offered a new platform for functionalized self-organising BTBT. Abstract : The study of a [1]benzothieno[3, 2- b ][1]benzothiophene (BTBT) derivative decorated with hexyl chains functionalized with hydroxyl end groups is reported. A rapid and inexpensive functionalization of the BTBT in positions 2 and 7 has been developed. This compound is able to self-organize into a lamellar structure through σ–π stacking and van der Waals interactions but also through hydrogen bonding interactions. The hydrogen-bonded network controls the interlamellar region in terms of organization and stability. The liquid-crystal phase and structural changes observed by DSC have been characterized using an original approach combining FTIR and powder XRD measurements as a function of temperature. Thermally evaporated diol based OFETs exhibited good mobilities of up to 0.17 cm 2 V −1 s −1 measured under an inert atmosphere but also in ambient air. The diol derivative is considered to be a very promising platform for the design of new functionalized BTBT.